2008
DOI: 10.1242/dmm.000596
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing stromal cell dynamics in different tumor microenvironments by spinning disk confocal microscopy

Abstract: SUMMARYThe tumor microenvironment consists of stromal cells and extracellular factors that evolve in parallel with carcinoma cells. To gain insights into the activities of stromal cell populations, we developed and applied multicolor imaging techniques to analyze the behavior of these cells within different tumor microenvironments in the same live mouse. We found that regulatory T-lymphocytes (Tregs) migrated in proximity to blood vessels. Dendriticlike cells, myeloid cells and carcinoma-associated fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
217
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(224 citation statements)
references
References 59 publications
2
217
0
Order By: Relevance
“…However, breast cancer also involves characteristic changes in the ECM and the tumor microenvironment (9)(10)(11)(12). For example, collagen I is enriched and aligned at the stromal border in breast tumors (10,13), changes in collagen I organization are independent negative prognostic indicators (14), and increased collagen I crosslinking accelerates progression in experimental cancer models (15).…”
mentioning
confidence: 99%
“…However, breast cancer also involves characteristic changes in the ECM and the tumor microenvironment (9)(10)(11)(12). For example, collagen I is enriched and aligned at the stromal border in breast tumors (10,13), changes in collagen I organization are independent negative prognostic indicators (14), and increased collagen I crosslinking accelerates progression in experimental cancer models (15).…”
mentioning
confidence: 99%
“…Using color-coded imaging of the TME, Egeblad et al observed that regulatory Tlymphocytes migrated to blood vessels. These authors observed that stromal cells had higher motility in the TME at the tumor periphery than within the tumor mass (22).…”
Section: Imaging the Critical Role Of Stromal Cells In Metastasismentioning
confidence: 95%
“…Color-coded imaging of the TME has enabled important discoveries of its cellular components (22,23). Using color-coded imaging of the TME, Egeblad et al observed that regulatory Tlymphocytes migrated to blood vessels.…”
Section: Imaging the Critical Role Of Stromal Cells In Metastasismentioning
confidence: 99%
“…(130-132) Different components of tumor stroma similarly affect the progression of the tumor. As tumors develop and progress, they undergo dramatic morphological changes (133,134), which also involves the stroma (133,(135)(136)(137). The importance of stage-specific changes of the stroma is not yet completely comprehensible.…”
Section: Csc Conceptmentioning
confidence: 99%